A Literature Review: Strategies to Teach English as A Foreign Language - Dhea Saragih; Tiara Lidya Rosarina Hutajulu; Samuel Parlindungan Girsang (Journal on Education, 2023)
This research aims to further examine strategies that can be used to teach English as a foreign language. The method that the researchers applied to this research was qualitative research with literature review design. The data sources in this research are limited according to research topic taken from books, websites, and supporting journals. Researchers discovered several teaching strategies for teaching English as a foreign language, including complete learning, recitation, drill, ice breaking, recalling memory, brainstorming, class discussion, games, listening and reading, paragraph writing, filling blanks, English camp, assembly, cooperative learning, problem-based learning, project-based learning, basic materials teaching, implementation of good habits, fun english learning, focus on academic language, literacy and vocabulary, link background knowledge and culture to learning, promote classroom interaction, increase comprehensible input and language output, and stimulate higher-order thinking skills and use of learning strategies. Therefore, the use of effective strategies in teaching English as a foreign language is expected to create new innovations for learners’ success in learning English.